Histopathological spectrum in cases of abnormal uterine bleeding: a cross sectional study in tertiary care hospital in Tripura - Reang, Noni Gopal; Bhaumik, Arup; Banerjee, Alpana; Roy, Jayanta; Datta, Abhijit (International Journal of Research in Medical Sciences, 2023)
Background: Majority women encounter abnormal uterine bleeding in their life where the causes are not limited to cancer even unknown. The actual cause has not been studied in north-east part of India. This data is scarce in State of Tripura. The present study aims to find out histomorphological patterns of AUB reported in AGMC & GBP Hospital in a calendar year. Methods: A cross sectional study was conducted over 2 calendar year from 2021 to 2022 where the cases of AUB irrespective of age, who had undergone endometrial biopsy, endometrial curettage and hysterectomy in Obstetrics and Gynaecology department, AGMC were examined histomorphologically in the dept of Pathology, AGMC. Data were collected in predesigned proforma and analysed using SPSS 21.0 and expressed in both descriptive and inferential statistics. Ethical approval was taken. Results: Total 220 cases of AUB specimens were examined. Among the reported AUB cases, the mean age is 42.5±7.42 year. Overall, 16.81% of the cases of AUB shows normal tissue pattern and 83.19% with abnormal endometrial tissue. Out of 220 sample of AUB, the commonest cause was leiomyoma (20.45%) followed by endometrial hyperplasia (17.27%), adenomyosis (14.54%), mixed tumour lesion (9.09%), endometrial carcinoma (4.54%) and 1.35% shows cervical cancer. Conclusions: Study concluded that In Tripura, majority AUB cases are due to leiomyoma, endometrial hyperplasia, adenomyosis and mixed inflammation indicating proper screening during reproductive stage of the women.